Peningkatan Proses Pembelajaran Tematik Terpadu Tema 3 Menggunakan Model Koperative Learning Tipe Namber Head Together di kelas III SD Negeri 02 Batang Limpaung Solok Selatan - Fitri, Lili Elsa; Mayarnimar, Mayarnimar (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2020)
This research purposed to describe the improvement of integrated thematic learnig process using cooperative learning model namber head together type in Elementary School. This research is a classroom action research with qualitative and quantitative approaches. Subjects were teachers and 32 students. This research was consists of two cycles. The first cycle consists of two meetings and the second cycle consists of one meeting with stages of planning, implementation, observation, and reflection . The result of planning observation in cycle I  is 81,95% (B) and it increase to be 94,4% (SB)  in cycle II. The result of teacher aspect observation in cycle I is 83,35% (B)  and it increase to be 94,4% (SB) in cycle II. The result of student aspect observation in cycle I is 80,55% (C)  and it increase to be 91,7% (SB) in cycle II. The learning outcomes in cycle I is 71,8 (C) and it increase to be 90,62 (B) in cycle II. The research showed the cooperative learning model namber head together type can improve the integrated thematic learnig process in Elementary School.